Complex impedance and ionic conduction of single-crystalline BaTiO3. (13th November 2016) - Shiga, Keiji; Katsui, Hirokazu; Goto, Takashi
ABSTRACT: Dielectric properties of single-crystalline BaTiO3 in the direction to <001> were investigated by impedance spectroscopy. The complex plane plots showed high- and low-frequency semicircles and an inclined spike at 548–648 K. The spectroscopic plots of M ″ comprised a single relaxation peak at 10 2 –10 4 Hz, whereas those of Z ″ exhibited a peak at high frequencies (10 2 –10 4 Hz), a low-frequency peak, and dispersion. The high-frequency relaxation was attributed to the ferroelectric bulk. The low-frequency peak and dispersion were associated with the charge transfer and the Warburg impedance, respectively. The low-frequency impedance response implied the ionic conduction of BaTiO3 .